2019
DOI: 10.1002/ejp.1384
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar range of motion in chronic low back pain is predicted by task‐specific, but not by general measures of pain‐related fear

Abstract: Background Most studies fail to show an association between higher levels of pain‐related fear and protective movement behaviour in patients with chronic low back pain (CLBP). This may be explained by the fact that only general measures of pain‐related fear have been used to examine the association with movement patterns. This study explored whether task‐specific, instead of general measures of pain‐related fear can predict movement behaviour. Methods Fifty‐five patients with CLBP and 54 healthy persons perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 67 publications
9
61
1
7
Order By: Relevance
“…Our results support the evolving evidence that fear avoidance beliefs and associated pain- [34]. In line with the current study, that study observed a significant negative relationship between movement-specific pain-related fear, reflected by the PHODA-lift item, and lumbar motion during a lifting task, supporting the construct validity of the PHODA-lift item.…”
Section: The Impact Of Pain-related Fear On Spinal Motion In Pain-fresupporting
confidence: 92%
See 2 more Smart Citations
“…Our results support the evolving evidence that fear avoidance beliefs and associated pain- [34]. In line with the current study, that study observed a significant negative relationship between movement-specific pain-related fear, reflected by the PHODA-lift item, and lumbar motion during a lifting task, supporting the construct validity of the PHODA-lift item.…”
Section: The Impact Of Pain-related Fear On Spinal Motion In Pain-fresupporting
confidence: 92%
“…To compare the actual data in pain-free adults with similar analyses recently performed in chronic LBP patients [34], we conducted the following complementary analyses: (1)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…whether less protective movement and postural patterns resulted in changes to pain or activity limitation, vice versa, or whether changes in both had a separate common cause) remain unknown. Carefully designed experimental and mediational studies, that include psychological factors known to be important for people with disabling NSLBP, such as pain catastrophising, fear and pain self-efficacy, would be required to make causal inferences (Lee et al, 2017;Matheve, De Baets, Bogaerts, & Timmermans, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological factors (such as pain catastrophising, fear and pain self-efficacy) have been shown to relate more to improved pain or activity limitation than physical parameters such as movement or abdominal muscle function (Mannion, Caporaso, Pulkovski, & Sprott, 2012;Mannion et al, 2001;Nordstoga, Meisingset, Vasseljen, Nilsen, & Unsgaard-Tondel, 2019). Psychological factors have also been shown to influence the embodiment of cautious and protective movement behaviours (Matheve et al, 2019;Olugbade, Bianchi-Berthouze, & Williams, 2019;Osumi et al, 2019) and mediate improvement (Lee et al, 2017;Liew et al, 2020;Mansell, Kamper, & Kent, 2013;Smeets, Vlaeyen, Kester, & Knottnerus, 2006). It may be that threat reduction, following the safe completion of previously painful, feared, or avoided activities perceived as dangerous or damaging, led to clinical improvement, irrespective of whether this was related to changes in movement or posture (Mannion et al, 2012;Steiger et al, 2012).…”
Section: Discussionmentioning
confidence: 99%